A Unique Heterozygous CARD11 Mutation Combines Pathogenic Features of Both Gain- and Loss-of-Function Patients in a Four-Generation Family - Desjardins, Marylin; Arjunaraja, Swadhinya; Stinson, Jeffrey R.; Dorjbal, Batsukh; Sundaresan, Janani; Niemela, Julie; Raffeld, Mark; Matthews, Helen F.; Wang, Angela; Angelus, Pamela; Su, Helen C.; Mazer, Bruce D.; et al. (Frontiers in Immunology, 2018)
CARD11 is a lymphocyte-specific scaffold molecule required for proper activation of B- and T-cells in response to antigen. Germline gain-of-function (GOF) mutations in the CARD11 gene cause a unique B cell lymphoproliferative disorder known as B cell Expansion with NF-κB and T cell Anergy (BENTA). In contrast, patients carrying loss-of-function (LOF), dominant negative (DN) CARD11 mutations present with severe atopic disease. Interestingly, both GOF and DN CARD11 variants cause primary immunodeficiency, with recurrent bacterial and viral infections, likely resulting from impaired adaptive immune responses. This report describes a unique four-generation family harboring a novel heterozygous germline indel mutation in CARD11 (c.701-713delinsT), leading to one altered amino acid and a deletion of 4 others (p.His234_Lys238delinsLeu). Strikingly, affected members exhibit both moderate B cell lymphocytosis and atopic dermatitis/allergies. Ectopic expression of this CARD11 variant stimulated constitutive NF-κB activity in T cell lines, similar to other BENTA patient mutations. However, unlike other GOF mutants, this variant significantly impeded the ability of wild-type CARD11 to induce NF-κB activation following antigen receptor ligation. Patient lymphocytes display marked intrinsic defects in B cell differentiation and reduced T cell responsiveness in vitro. Collectively, these data imply that a single heterozygous CARD11 mutation can convey both GOF and DN signaling effects, manifesting in a blended BENTA phenotype with atopic features. Our findings further emphasize the importance of balanced CARD11 signaling for normal immune responses.